Sedation in specialized palliative care: A cross-sectional study. - Christel Hedman; Aldana Rosso; Ola Häggström; Charlotte Nordén; Carl Johan Fürst; Maria E C Schelin (PLoS ONE, 2022)
Background Palliative sedation is used to relieve refractory symptoms and is part of clinical practice in Sweden. Yet we do not know how frequently this practice occurs, how decision-making takes place, or even which medications are preferentially used. Objectives To understand the current practice of palliative sedation in Sweden. Methods We conducted a retrospective cross-sectional medical record-based study. For 690 consecutive deceased patients from 11 of 12 specialized palliative care units in the southernmost region of Sweden who underwent palliative sedation during 2016, we collected data on whether the patient died during sedation and, for sedated patients, the decision-making process, medication used, and depth of sedation. Results Eight percent of patients were sedated. Almost all (94%) were given midazolam, sometimes in combination with propofol. The proportions of sedation were similar in the patient groups with and without cancer. The largest proportion of the sedated patients died in inpatient care, but 23% died at home, with specialized palliative home care. Among the patients with a decision to sedate, 42% died deeply unconscious, while for those without such a decision the corresponding figure was 16%. In only one case was there more than one physician involved in the decision to use palliative sedation. Conclusion 8% of patients in specialized palliative care received palliative sedation, which is lower than international measures but much increased compared to an earlier Swedish assessment. The level of consciousness achieved often did not correspond to the planned level; this, together with indications of a scattered decision process, shows a need for clear guidelines.